Proceedings of the 3rd Annual International Seminar and Conference on Global Issues (ISCoGI 2017) 2019
DOI: 10.2991/iscogi-17.2019.45
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Religiosity on Organizational Citizenship Behaviour (A Case Study on Teachers of Roudlotus Saidiyyah Foundation)

Abstract: Religiosity is closely associated with religious activities; not only performing rituals (worship) but also on other activities. Religiosity can predict how a person's work performance is. The purpose of this study is to analyze the level of religiosity of a person through five dimensions; ritual, ideological, intellectual, experience and the dimension of consequences, and to analyse religiosity's effect on organizational citizenship behavior (OCB). The analytical tool used to test the effect of research varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Inconsistencies from previous studies also occurred in some studies conducted (Pratono, 2019) which revealed that the variable Religiosity had a positive and significant effect on OCB, while the research conducted (Ariyanti, 2019) found that the variable Religiosity had a negative and significant effect on OCB.…”
Section: A Introductionmentioning
confidence: 87%
“…Inconsistencies from previous studies also occurred in some studies conducted (Pratono, 2019) which revealed that the variable Religiosity had a positive and significant effect on OCB, while the research conducted (Ariyanti, 2019) found that the variable Religiosity had a negative and significant effect on OCB.…”
Section: A Introductionmentioning
confidence: 87%
“…But in this study, researchers looked at religiosity factors in general. Therefore, researchers want to see the influence of each of the dimensions that exist in religiosity [29]. So the hypothesis in this study on figure 1 are: H1 Dimension of participation has an influence on OCB.…”
Section: Religiosity and Ocbmentioning
confidence: 98%
“…Religious activities do not only occur when a person performs a ritual (worship) but also performs other activities that are driven by final strength (36). This is not only related to visible and visible activities but also the invisible ones that occur in one's heart.…”
Section: Religious Social Activities and The Influence Of The Ngopi C...mentioning
confidence: 99%